Is It Time to Review our Educational Program for the Electrocardiography Operators? - Habibollah Saadat; Hossein Tajdini; Zahra Saadat; Vahid Eslami; Mehdi Sheibani; Babak Sharifkashani; Roxana Sadeghi; Isa Khaheshi (Publisher: Shahid Beheshti University of Medical Sciences, 2017)
No abstract available.